The Morisky Method for Measuring Medication Adherence in Older Adults With Chronic Diseases: A Cross‐Sectional Study - Shokofeh Afkhami; Farkhondeh Asadi; Hassan Emami; Azam Sabahi (Health Science Reports)
ABSTRACT Background and Aims In the elderly population, the prevalence of chronic diseases and the necessity for supportive and medication treatments are increasing, making medication adherence a crucial factor in enhancing their quality of life. Methods This study conducted a comprehensive descriptive‐analytical survey on older adults aged over 65 with chronic diseases, who were visiting a specialized diabetes clinic in YAZD in 2023. The clinic provides treatment for elderly diabetic patients as well as those with chronic diseases resulting from or concurrent with diabetes, managed by internal medicine specialists and endocrinologists. The participants had been taking medication for more than 6 months and were suffering from chronic conditions such as asthma, hypertension, diabetes, chronic cardiovascular disease, liver cirrhosis, stroke, and vascular heart disease, with normal cognitive function. Medication adherence was assessed to determine the level of adherence. Data were analyzed using SPSS version 20.0, utilizing logistic regression. Results A total of 196 participants took part in the study. The average medication knowledge score was 14.7 ± 3.5, the average depression score was 8.1 ± 2.4, the average health literacy score was 7.5 ± 1.6, and the average self‐efficacy score was 29.1 ± 5. Logistic regression analysis revealed that more than half of the participants (58.7%) lacked medication adherence. The analysis also indicated that the presence of a spouse had a significant effect on medication adherence (p‐value = 0.038), along with health literacy (p‐value = 0.002) and self‐efficacy (p‐value = 0.000), which had the most significant impact on medication adherence. Conclusion The findings suggest that self‐efficacy, health literacy, and the presence of a spouse are crucial factors influencing medication adherence in older adults with chronic diseases. These factors can shape the beliefs, attitudes, and behaviors of older adults regarding medication adherence and affect their health outcomes and quality of life. Therefore, interventions aimed at improving medication adherence in this population should consider these factors and attention to the specific needs and preferences of older adults and their spouses or family members.